Analysis Of The Use Of Smart TV as A Media For Arabic Learning At Insan Amanah Junior High School - Fikri, Alvian Izzul; Nur Hasaniyah; Abdul Muntaqim Al-Anshory (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The purpose of this study is to analyze the use of Smart TV as a learning tool for the Arabic language at Insan Amanah Junior High School Malang. The research method used is qualitative, employing a case study approach. In the era of Industry 5.0, it's crucial to integrate technology into the learning process to facilitate interaction between teachers and students. Smart TVs, being modern technological devices, offer various interactive features that can be leveraged to support Arabic language learning. Data for this study was collected through direct observation, interviews with teachers and students, and analysis of documentation related to the use of Smart TV in teaching and learning activities. The study results indicate that using Smart TV can enhance student motivation and participation in learning Arabic. Features such as educational applications, learning videos, and internet access provide convenience in delivering material and enriching learning resources. Additionally, the study found that the success of using Smart TV as a learning tool is greatly influenced by the clarity of the purpose of use, user familiarity with the technology, and clear guidelines for its use. Therefore, Smart TV is an effective and efficient medium for improving the quality of Arabic language learning in the digital era.